ANALYSIS OF SIGNS AND MEANINGS IN SARIAYU HIJAB HAIRCARE ADVERTISEMENTS (Semiotic Analysis of Instagram Account @sariayuhijab) - Izzarine Nurdiaz Pramudita; Muhammad Edy Susilo; Christina Rohayanti (The Indonesian Journal of Communication Studies, 2017)
Sariayu Hijab is a company that takes advantage the presence of Instagram as a social media platform to promote and advertise their products. In this regard, there are particular methods that differ from conventional advertisements, especially in terms of visual language, form and presentation. This research aims to reveal the signs and meanings of Sariayu advertisements shown on their Instagram account @sariayuhijab. The method used in this research is qualitative while using Semiotics Analysis by Roland Barthes, which attempts to analyze advertisements seen from three aspects, such as denotation, annotation and myth. Another theory applied for this research is Commodification Theoretical Concept that plays a role in understanding how Sariayu Hijab advertisements are presented. The data are taken from six advertising samples in pictures uploaded on their Instagram account @ Sariayuhijab from June to December 2016. The result of the research shows that Sariayu Hijab uses a Commodification of Islam that appears in the form of values, attribute and other signs as presented on the images. The Islamic value as commodity can be recognized from the use of religious sign in the form of textual advertisement. Other than that, a Commodification of green lifestyle is also noticeable in accordance with their thematic products, for instance the use of natural ingredients comprising fruits and vegetables. Sariayu Hijab considers the use of religious visual sign, which deems necessary to apply on their advertisement as a marketing strategy so that public will be intrigued in buying and wearing the products. This strategy is hence considered as a commodification that highlights a change from functionality to commercial commodity for capitalistic purposes vis-à-vis dogmatic belief.